1994
DOI: 10.1007/bf00003438
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and induction of cytochrome P450 1A1 in the rainbow trout brain

Abstract: Cytochrome P450 (CYP) 1A1 participates in the activation as well as detoxification of environmental pollutants such as aromatic hydrocarbons. This CYP form is also efficiently induced by aromatic hydrocarbons. The presence of CYP 1A1 in the brain might thus be of physiological and toxicological importance. In the present investigation on rainbow trout, the distribution of 7-ethoxyresorufin-O-deethylase (EROD) activity, a cytochrome CYP 1A1 catalyzed reaction, was measured in whole tissue homogenates from brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Furthermore, in the present study, EROD activity in microsome was slightly lower than that in tissues. This result was confirmed by Andersson and Goksyr (1994), who found that EROD activity in the whole‐brain homogenate of rainbow trout in a control and a b‐naphthoflavone exposure group was higher than that of microsome in the whole‐brain tissue. At present, no study detecting GST activity in subcellular fractions of bivalves has been found.…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, in the present study, EROD activity in microsome was slightly lower than that in tissues. This result was confirmed by Andersson and Goksyr (1994), who found that EROD activity in the whole‐brain homogenate of rainbow trout in a control and a b‐naphthoflavone exposure group was higher than that of microsome in the whole‐brain tissue. At present, no study detecting GST activity in subcellular fractions of bivalves has been found.…”
Section: Discussionsupporting
confidence: 74%
“…Therefore, CYP protein in the olfactory bulbs should be constitutively expressed and also highly inducible in response to any acute xenobiotic exposure. Indeed, the presence of constitutive CYP1A1 in fish olfactory systems has been confirmed (Andersson and Goksøyr, 1994;Monod et al, 1994Monod et al, , 1995Ortiz-Delgado et al, 2002), and CYP1A1 immunoreactivities and enzyme activities are induced in the olfactory organs in fish exposed to xenobiotics (Goksøyr and Förlin, 1992;Smolowitz et al, 1992).…”
Section: Discussionmentioning
confidence: 94%
“…There is also in vivo evidence of enhanced TA metabolism in brains of offspring born to PCB-exposed dams (59), and there are reports that TCDD treatment decreases brain levels of TRP and 5-OH-TA in rats (60). Given that AhR (61) and ARNT (62) have been detected in rats brains using in situ hybridization techniques and the induction of brain CYP1A1 gene expression by HAHs and PAHs in rats (63), humans (64), and trout (65) has been demonstrated, it is possible that potentially serious physiological and toxicological consequences could occur as a result of a perturbation of TRP metabolism by AhR ligands, particularly in the brain.…”
Section: Discussionmentioning
confidence: 99%